Brazilian conservatism today: its affiliation to the neoliberal agenda - Silva, Amanda Sales (Argumentum, 2021)
The article clarifies the relationships within Brazilian conservative ideology today, based on the direct links between the Brazilian Right and the objectives of the neoliberal agenda. In the light of historical dialectical materialism and through exploratory research, our objective is to explain the material basis of the conservatism that has gained such force on the national political scene.